Compressive Strength and Bonding Performance of Concrete Beams Strengthened with GFRP Plates - Abdul Kudus, Sakhiah; Mohd Zuki, Sharifah Salwa; Shahidan, Shahiron (International Journal of Integrated Engineering, 2025)
This study aims to test the bond strength and the structural response of concrete beams reinforced with Glass Fiber Reinforced Polymer (GFRP) plates. The experimental program included a total of 41 prisms, of which 12 were tested for compressive strength, and 25 were configured into beams with four-point loading systems, referred to as the GFRP beam set. In total, six beams attached GFRP plates of 50 mm x 100mm and 200 mm (GFRPP-50 and GFRPP-100), while three beams served as control specimens without externally bonded plates. The findings verified that when GFRPP-100 was used as reinforcement, its ultimate load-bearing capacity increased by 137% compared to the controls, being substantially stronger than the other beams. The research emphasizes the role of the epoxy adhesives described in the methods section, including the bonding surface preparation, enabling a cohesive bond connection. GFRP confinement may be used as an innovative strengthening method instead of traditional methods which results in improved structural performance. Further investigations should look into the effects of differing environmental exposures and durations of loads applied on the durability of GFRP-reinforced beams over time. This study provides evidence to facilitate the acceptance of GFRP as an efficient reinforcement tool that improves the serviceability lifespan.